2017
DOI: 10.3390/v9100264
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Leaf Curl New Delhi Virus: An Emerging Virus Complex Threatening Vegetable and Fiber Crops

Abstract: The tomato leaf curl New Delhi virus (ToLCNDV) (genus Begomovirus, family Geminiviridae) represents an important constraint to tomato production, as it causes the most predominant and economically important disease affecting tomato in the Indian sub-continent. However, in recent years, ToLCNDV has been fast extending its host range and spreading to new geographical regions, including the Middle East and the western Mediterranean Basin. Extensive research on the genome structure, protein functions, molecular bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
103
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(106 citation statements)
references
References 95 publications
3
103
0
Order By: Relevance
“…that ≥91% and ≥94% nucleotide sequence identity account for begomovirus species and strain demarcation, respectively (Brown et al ., ). Therefore, these isolates constitute a new strain of this virus, for which the name ES (ToLCNDV‐ES) was proposed (Moriones et al ., ). Evolutionary relationships among ToLCNDV sequences used in this study showed that all the Italian isolates are closely related to those from Spain, Tunisia and Morocco and thus a common origin can be assumed for these isolates, identifiable in ToLCNDV‐ES.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…that ≥91% and ≥94% nucleotide sequence identity account for begomovirus species and strain demarcation, respectively (Brown et al ., ). Therefore, these isolates constitute a new strain of this virus, for which the name ES (ToLCNDV‐ES) was proposed (Moriones et al ., ). Evolutionary relationships among ToLCNDV sequences used in this study showed that all the Italian isolates are closely related to those from Spain, Tunisia and Morocco and thus a common origin can be assumed for these isolates, identifiable in ToLCNDV‐ES.…”
Section: Discussionmentioning
confidence: 97%
“…Evolutionary relationships among ToLCNDV sequences used in this study showed that all the Italian isolates are closely related to those from Spain, Tunisia and Morocco and thus a common origin can be assumed for these isolates, identifiable in ToLCNDV‐ES. As ToLCNDV rapidly spread in a few years within the Mediterranean area, the low level of variability found among isolates supports the hypothesis of the founder effect associated with a population bottleneck during the spread to this new area (Moriones et al ., ). As reported by different authors (Juárez et al ., ; Mnari‐Hattab et al ., ; Luigi et al ., ; Panno et al ., ; Moriones et al ., ), ToLCNDV in the Mediterranean basin found zucchini squash as its elected host.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, these three viruses produced consistent symptoms and have been shown to be transmissible. Begomoviruses are phloem-limited viruses and therefore generally considered not seed-transmitted, with a few possible exceptions (Mink, 1993;Bos, 1999) Yes Reported to be persistently transmitted by Bemisia tabaci (Rosen et al, 2015;Moriones et al, 2017) Genus, Virus Acronym Biology of the pests All viruses considered in the present categorisation are transmitted by vegetative propagation (via tubers).…”
mentioning
confidence: 96%